Espaços livres públicos de lazer: uma análise configuracional das desigualdades no acesso para os grupos de renda e raça de Juiz de Fora (MG) - Araújo, Blenda Mayra Viana de (2021)
Public open spaces for leisure are great promoters of sociability and diversity in urban life. The benefits extend beyond the social sphere, being able to have a positive impact on the environmental quality of cities and the physical and mental health of their populations. However, public open spaces for leisure are rarely a priority in public investments. As an aggravating factor, the distribution of spaces and the consequent access to public leisure is differentiated, revealing harm to the population in the enjoyment of leisure and recreation in public domain spaces. In this perspective, the objective of the study was to verify the offer and compare the level of access from the urban configuration to public open spaces for leisure for the different income and race strata of the population in the city of Juiz de Fora (MG). The hypothesis is tested that in areas with medium-high incomes, there is a greater offer and consequent ease of access to public open spaces for leisure. The methodology applied was based on public open spaces for leisure demarcated by the Participative Master Plan and Cadastral Plan of Juiz de Fora. It was done quantitative spatial analysis of the distribution and supply of spaces (Index of Green Leisure Areas – IAVL and Kernel Density Estimate), as well as syntactic analysis of the urban configuration through the use of Spatial Syntax, correlation analysis of spatial and social data, and comparison analysis between morphologically distinct regions of the city. The results showed a distribution of spaces concentrated in the downtown area, which is also the place where there is a higher income. The calculated IAVL pointed out that most of the territory presents indices smaller than one square meter of public open space for leisure per inhabitant, indicating a low offer of spaces. The offer, confronted with income and race, showed no direct relationships. However, the possibilities of accessing spaces were greater where the income level was higher and where the majority population was white, whose configurational pattern was more integrated. The most segregated areas were characterized by a low-income population, black and brown, where access to open public spaces for leisure was more difficult.